2018
DOI: 10.1111/1541-4329.12153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Integrating Food Science Lessons in High School Biology Curriculum in Comparison to High School Chemistry Curriculum

Abstract: Historically, high school chemistry has been the predominate venue for the introduction of food science curriculum to students. With the current decline in chemistry as a required course for graduation, the possibility of exposure to food science in high school could equally decline. The purpose of this research was to determine if high school students in a biology class without a chemistry background could comprehend eight basic food science principles equally as well as students in a chemistry class that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Based on Bandura's concept of self‐efficacy, more professional development training in STEM‐related fields would strengthen the teachers’ ability to teach STEM concepts in class, leading to a higher feeling of competency and ability to create a better learning environment. Using the success of the comparison of the effectiveness of food science lessons with biology versus chemistry students (Stringer et al, ), future research should also be conducted to measure FCS students’ self‐efficacy in STEM‐related concepts after completing the STEM‐enhanced Food and Nutrition Science 1 course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Bandura's concept of self‐efficacy, more professional development training in STEM‐related fields would strengthen the teachers’ ability to teach STEM concepts in class, leading to a higher feeling of competency and ability to create a better learning environment. Using the success of the comparison of the effectiveness of food science lessons with biology versus chemistry students (Stringer et al, ), future research should also be conducted to measure FCS students’ self‐efficacy in STEM‐related concepts after completing the STEM‐enhanced Food and Nutrition Science 1 course.…”
Section: Discussionmentioning
confidence: 99%
“…Research in STEM and success in content learning has been successful in the secondary and postsecondary level (Duffrin, ; Stringer, Hendrix, Swortzel, Williams, & Schilling, ). However, STEM is already part of Food Science, and these studies do not address the purposeful integration of STEM, but rather the positive results of a STEM‐related curriculum.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This simple kitchen chemistry experiment entails ideas about sugar, acidity, senses, calories, and health. Kitchen chemistry is an educational approach that invites people to learn about the sciences behind food by cooking food, using typical kitchen appliances. , Some showed that this pedagogy may raise interest in chemistry or biology fields, , while others anticipate it to raise the general interest in all sciences among the public, especially among beginners and novices in science . As increasing efforts are being made to introduce kitchen chemistry into precollege learning experiences to attract students into STEM, we need studies to investigate to what extent and how kitchen chemistry may boost STEM affinity, and whether this boost is or is not confined to biology and chemistry subjects.…”
Section: Introductionmentioning
confidence: 99%
“…However, first-generation-educated ethnic minority students, particularly Latinos, are gravely underrepresented in the food, agricultural, natural resources, and human sciences disciplines (McKim et al, 2017). There is a dire need for fully qualified, culturally and linguistically resonant graduates with degrees in food-related sciences to pursue careers in the food and agricultural workforce (Goecker et al, 2015;Stringer et al, 2019) who will tackle our nation's most pressing 1021454P HPXXX10.…”
mentioning
confidence: 99%
“…However, first-generation-educated ethnic minority students, particularly Latinos, are gravely underrepresented in the food, agricultural, natural resources, and human sciences disciplines (McKim et al, 2017). There is a dire need for fully qualified, culturally and linguistically resonant graduates with degrees in food-related sciences to pursue careers in the food and agricultural workforce (Goecker et al, 2015; Stringer et al, 2019) who will tackle our nation’s most pressing health problems, such as obesity. Increasing the number of qualified Latino public health professionals including registered dietitian nutritionists (RDNs) may be a way to address Latino health through the provision of linguistic and culturally congruent care (Heiss et al, 2012; O’Toole et al, 2019).…”
mentioning
confidence: 99%